2022
DOI: 10.1071/ma22005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of dermatophytes: from microscopy to direct PCR

Abstract: Dermatophyte fungi are a common cause of skin, nail and hair infections globally, ranging from mild to cosmetically disfiguring, or even invasive infections in rare cases. Specimens requiring fungal microscopy and culture for suspected dermatophyte infection make up a significant portion of the workload in diagnostic microbiology laboratories. Whilst still considered the gold standard, a dermatophyte culture-based method is labour intensive, has poor sensitivity, slow result turnaround time and requires signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Identified cost as (primary, secondary, tertiary) decision factor Although microscopic examination is the gold standard to diagnose dermatophytes, differentiating dermatophyte hyphae/elements from other fungi requires a high scale of experience (Kidd and Weldhagen, 2022). The Candida genera were the most dominant in all hospitals, agreeing with the global estimates of fungal infections (Bongomin et al, 2017).…”
Section: Diagnostic Criteria and Qualitymentioning
confidence: 63%
See 1 more Smart Citation
“…Identified cost as (primary, secondary, tertiary) decision factor Although microscopic examination is the gold standard to diagnose dermatophytes, differentiating dermatophyte hyphae/elements from other fungi requires a high scale of experience (Kidd and Weldhagen, 2022). The Candida genera were the most dominant in all hospitals, agreeing with the global estimates of fungal infections (Bongomin et al, 2017).…”
Section: Diagnostic Criteria and Qualitymentioning
confidence: 63%
“…All the participating hospitals rely on microscopic examination to diagnose this type of fungal infections, as shown in the results. The microscopic examination of dermatophytes has 90.5% accuracy ( Aboul-Ella et al., 2020 ) Although microscopic examination is the gold standard to diagnose dermatophytes, differentiating dermatophyte hyphae/elements from other fungi requires a high scale of experience ( Kidd and Weldhagen, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this may require special training and advanced equipment, the benefits of utilizing such techniques outweigh this hurdle. Several methods have been used in this regard including polymerase chain reaction (PCR) based on internal transcribed spacer (ITS) sequencing, real-time PCR, DNA microarray, and next-generation sequencing [98]. Currently, studies have shown that the best accuracy can be obtained by using both conventional and molecular techniques [97].…”
Section: Management Prospective and Alternative Treatmentsmentioning
confidence: 99%
“…Однако в некоторых случаях для видовой идентификации может потребоваться дополнительное изучение биохимических свойств выделенных культур дерматофитов. Поэтому видовая идентификация дерматофитов на основе изучения фенотипических свойств является трудоемким процессом, требующим больших затрат времени и высокой квалификации исследователей [7].…”
Section: Introductionunclassified